Cost-effectiveness of preimplantation genetic testing for aneuploidy for fresh donor oocyte cycles - Maria Facadio Antero, M.D; Bhuchitra Singh, M.D., M.P.H, M.S; Apoorva Pradhan, B.A.M.S., M.P.H; Megan Gornet, M.D; William G. Kearns, Ph.D; Valerie Baker, M.D., M.P.P; Mindy S. Christianson, M.D (Elsevier, 2021)
Objective: To determine whether in vitro fertilization (IVF) with preimplantation genetic testing for aneuploidy (PGT-A) is cost effective to achieve a live birth compared with IVF alone in fresh donor oocyte cycles. Design: Theoretical cost-effectiveness study. Setting: Not applicable. Patient(s): None. Intervention(s): Comparison between the cost of IVF with PGT-A vs. IVF alone to achieve a live birth. The model analyzed a hypothetical single fresh oocyte donor IVF cycle with PGT-A vs. IVF alone and followed the progression of a single embryo through the different decision nodes. Cost estimates assigned to each clinical event were based on data obtained from the literature and institutional costs. Main Outcome Measure(s): Cost per live birth. Result(s): In the base-case analysis, IVF with PGT-A was not cost effective in fresh donor oocyte cycles when compared with IVF alone to achieve a live birth. The cycles using PGT-A cost an additional $6,018.66. The incremental cost-effectiveness ratio was found to be $119,606.59 per additional live birth achieved with IVF with PGT-A. Monte Carlo simulations demonstrated that IVF with PGT-A was not cost effective in nearly all iterations. Conclusion(s): PGT-A in fresh donor oocyte IVF cycles is not cost effective compared with IVF alone over a wide range of probabilities and costs.